1998
DOI: 10.1007/s004410051002
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis in human salivary glands visualized by high-resolution scanning electron microscopy

Abstract: The luminal membrane of salivary acinar cells creates a specialized cell surface area that accepts exocytosis and undergoes dynamic changes during secretion. These changes were visualized three-dimensionally from both the inside and outside of the cell in human parotid and submandibular glands, by application of in vitro secretory stimulation and then of OsO4 maceration to remove cytoplasmic organelles by varying degrees. In control glands treated without secretagogues, the luminal surface of serous acinar cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
(49 reference statements)
1
24
0
Order By: Relevance
“…We sought to determine whether the uptake of plasmid DNA into the acini could be enhanced. It has been suggested that, during exocytosis, membranes delivered during the release of the secretory granules are retrieved by compensatory endocytosis (3,13,36,42). To test whether this process occurs in rat SMGs, we Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We sought to determine whether the uptake of plasmid DNA into the acini could be enhanced. It has been suggested that, during exocytosis, membranes delivered during the release of the secretory granules are retrieved by compensatory endocytosis (3,13,36,42). To test whether this process occurs in rat SMGs, we Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus it is tempting to speculate that the initial phase of exocytosis induced by Ca 2ϩ ramps identified in the present study reflects recruitment of the minor pathway. Indeed, ultrastructural studies of parotid and submandibular salivary glands have demonstrated the presence of small-diameter vesicles (Ͻ150 nm) at the subluminal face of apical membrane or on or around ZSGs (23,27). However, it is also possible that transient fusion of ZSGs, delayed fusion pore expansion, or retention of the phase-dense material underlies the initial phase reported by C m measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PKA-mediated regulation of the apical PMCA may give the cell further control over these important Ca 2ϩ -dependent effectors. This may be particularly important within the highly invaginated microvillar structures of the apical membrane, whereby the PMCA may be the only means for the clearance of local concentrations of Ca 2ϩ because of the absence of ER (37).…”
Section: Discussionmentioning
confidence: 99%